Physiography and climate of Trás-os-Montes - Gonçalves, Dionísio (2011)
Ultramafic rocks are rare lithotypes in Portugal. The main Portuguese ultramafic areas are restricted to the districts of Bragança and Portalegre, respectively located in the Trás-os-Montes (NE Portugal) and Alentejo (SE Portugal). The ultramafic rocks of the Trás-os-Montes are the largest and the richest in endemic species within Portugal. This text is a tour companion to the ultramafic rocks of northeastern Portugal. It contains, among other sections, a description of the physiography and climate of Trás-os-Montes, where the ultramafic rocks appear assembled in two massifs: Bragança, not far away from the Portuguese-Spanish border, and Morais, further south. (text slightly adapted from the Introduction section)